Pemetaan Usaha dan Identifikasi Tantangan Wirausaha di Dusun Sawangan, Desa Sawangan sebagai Rujukan Kebijakan Pemerintah Desa Sawangan - Navista Sri Octa Ujiantari; Aprila Kusuma Dewi (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2026)
Sawangan Sub-Village in Magelang Regency is an area with considerable economic potential based on agriculture and home-based businesses, but its sustainability still faces various structural and technical limitations. This study aims to obtain a comprehensive picture of the entrepreneurial profile, identify the main challenges faced, and formulate the needs for community business development at the sub-village level. The method used is a qualitative approach through in-depth interviews with 23 business actors with diverse socioeconomic backgrounds. Data collection was conducted through direct visits to homes and businesses, allowing for contextual observation of local economic dynamics. The results show that the majority of entrepreneurs are women aged 25 to 72, with a predominance of small-scale culinary businesses, grocery stores, and daily necessities trading. The challenges faced include fluctuations in the number of buyers, limited capital, competition with online sellers, unstable access to raw materials, and a lack of business legality. In addition, most business actors have not fully received relevant assistance or training, although some have participated in consumptive programs and simple technical training. These findings indicate an urgent need to strengthen entrepreneurial capacity through increased access to inclusive capital, licensing facilitation, provision of production facilities, and ongoing assistance in business management. In particular, mastery of digital marketing skills and product diversification are key to coping with changing consumption patterns and increasingly complex market competition. This study concludes that business mapping not only provides a snapshot of local economic conditions but also opens up opportunities for targeted strategic interventions to promote economic independence, strengthen the role of women in entrepreneurship, and enhance the sustainability of entrepreneurship in Sawangan Sub-Village.